2016
DOI: 10.1080/14656566.2016.1197204
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and treatment options for rheumatoid arthritis during pregnancy

Abstract: A great body of evidence suggest that hydroxychloroquine, sulfasalazine, and non-fluorinated steroids can be continued throughout pregnancy, while methotrexate and leflunomide should be discontinued 3 months before pregnancy. Continuation of TNFi during the first part of pregnancy should be considered when benefits outweigh the potential risk of teratogenicity. Data regarding other biologics are scant and, at present, they should be stopped before pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 95 publications
0
17
0
Order By: Relevance
“…Even though our study revealed relatively good tolerability and few effects on reproduction, LEF and MTX should be discontinued before a planned pregnancy according to the recommendation for RA treatment. 35,36…”
Section: Discussionmentioning
confidence: 99%
“…Even though our study revealed relatively good tolerability and few effects on reproduction, LEF and MTX should be discontinued before a planned pregnancy according to the recommendation for RA treatment. 35,36…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 100 pregnancies in patients with SLE, specifically addressing fetal loss related to circulating antiphospholipid antibodies, no fetal malformations were associated with HCQ use 18 . With 3 decades of study and clinical experience, HCQ has become one of the mainstays in controlling numerous immune conditions in pregnancy without fetal risk 19,20 .…”
Section: Antimalarials As a Rheumatic Disease Treatmentmentioning
confidence: 99%
“…It could be argued that women more often receive HCQ because HCQ is considered safe during pregnancy, in contrast to, for example, MTX, and might therefore be prescribed to pregnant women or to women with a desire to conceive 20 . It was indeed observed that women ≤ 50 years of age more often received HCQ; however, this effect was the same for men and therefore does not seem to be related to (wish for) pregnancy.…”
Section: Discussionmentioning
confidence: 99%